Drogas e internação: o encontro como mobilizador de perspectivas em educação e saúde - Novaes, Candice Cristiane Barros Santana (2015)
Inserted in the research line Training, Knowledge and Professional Development of the Graduate Master's Program in Education of Santa Maria / RS, the project is with the aim of understanding the drug user hospitalization process, in view of their experiments. The study is guided in Corrêa of references (2006, 2010), Karam (2007), Oliveira (2009), Preve (2010), Rolnik (1989), among others studying the prospects of drugs and the desire of cartography. It conducted interviews with drug users admitted to the Psychosocial Care Center - Alcohol and drugs in Palmas - Tocantins, in order to map the admission process from his lines. We came across 03 major routes transposing the drugs issue: police legal, psychiatric medical and religious. The readings we do and the echoes of our respondents always lead to one of these axes. Asserting the sensitivity to listen, to observe the progress and condition of the person you care for the health work process. Each encounter is unique, our needs are unique and it is up to the professional who deals with these needs, direct the care of individual and carefully.